Teorija tehno-slike Viléma Flusserja - Vaupotič, Aleš (Primerjalna književnost, 2014)
The text presents the idea of the technical image (techno-image) and the corresponding technical imagination (techno-imagination), from the point of view of its relevance for the literary scholarship. The main points of Flusser's methodology are discussed, among which the most important one is the strict distinction between the "old images" and the techno-images.
Keywords: Flusser, Vilém, 1920-1991; književnost in novi mediji; digitalna umetnost; vizualno mišljenje; tehniška slika